2016
DOI: 10.1111/1556-4029.13319
|View full text |Cite
|
Sign up to set email alerts
|

A City‐wide Investigation of the Isotopic Distribution and Source of Tap Waters for Forensic Human Geolocation Ground‐truthing

Abstract: Human geolocation is prefaced on the accuracy of the geographic precision of mapped isotopic values for drinking water. As most people live in cities, it becomes important to understand city water supplies and how the isotopic values uniquely reflect that city. This study investigated the isotopic distribution of δ H and δ O from sourced tap waters that were collected from across the Metro Vancouver (MV) area (n = 135). The results revealed that the isotopic values reflect their water sources with a range of 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…In the past decade, the spatial pattern and seasonal variability of stable isotope ratios in tap water has aroused attention in water resource studies, including regional water use and source diagnosis (e.g., Good et al, 2014;Jameel et al, 2016;Landwehr et al, 2014;Tipple et al, 2017;West et al, 2014). In addition, information on tap water isotope ratios has also been important in other fields including ecology, food, and forensic sciences (Bowen & Good, 2015;Ehleringer et al, 2008;Ueda & Bell, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, the spatial pattern and seasonal variability of stable isotope ratios in tap water has aroused attention in water resource studies, including regional water use and source diagnosis (e.g., Good et al, 2014;Jameel et al, 2016;Landwehr et al, 2014;Tipple et al, 2017;West et al, 2014). In addition, information on tap water isotope ratios has also been important in other fields including ecology, food, and forensic sciences (Bowen & Good, 2015;Ehleringer et al, 2008;Ueda & Bell, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, we note that measurements of the 87 Sr/ 86 Sr ratio of tap waters showed significant spatial and temporal variation in some locations (Table ). Previous studies have shown significant variation in the 87 Sr/ 86 Sr and other isotope ratios of tap water on the local scale due to water management practices . While the hair samples presented in Figure did not suggest travel movement based on the isotopic comparisons of the hair‐leachate pairs (i.e., difference in 87 Sr/ 86 Sr of pairs <0.00034), it is possible that spatial and temporal variation in the 87 Sr/ 86 Sr ratio of tap water added to the uncertainty in drawing geographic correlations between individuals and their environments.…”
Section: Resultsmentioning
confidence: 83%
“…Previous studies have shown significant variation in the 87 Sr/ 86 Sr and other isotope ratios of tap water on the local scale due to water management practices. 47,52,[65][66][67][68][69] While the hair samples presented in Given the known isotopic variability in water supply within some metropolitan areas, additional sampling resolution may be required in these locations to understand the geospatial relationships between the 87 Sr/ 86 Sr ratio of tap water and that of human hair.…”
Section: Relationships Between the Sr-isotope Ratios Of Hair And Tamentioning
confidence: 99%
“…As a whole, studies on isotopes in tap water are of great significance for enriching the understanding of tap water isotopes characteristics, environmental effect elements and water sources [23,24,39]. Stable isotopes (e.g., δ 2 H and δ 18 O) in tap water come to be important tools to understand the climate and environment characteristics in local area and water resources, monitor complex hydrological systems impacted by human activities, and reflect the state of regional water supply [24,43,44].…”
Section: Introductionmentioning
confidence: 99%